The relationship between patients' income and education and their access to pharmacological chronic pain management: A scoping review - Nicole Atkins; Karim Mukhida (Taylor & Francis Group, 2022)
Background Though chronic pain is widespread, affecting about one-fifth of the world's population, its impacts are disproportionately felt across the population according to socioeconomic determinants such as education and income. These factors also influence patients' access to treatment, including pharmacological pain management.Aim A scoping review was undertaken to better understand the association of socioeconomic factors with physicians' pain management prescribing patterns for adults living with chronic pain.Methods An electronic literature search was conducted using the EMBASE, CINAHL, SCOPUS, and Ovid MEDLINE databases and 31 retrieved articles deemed relevant for analyses were critically appraised.Results The available evidence indicates that patients' lower socioeconomic status is associated with a greater likelihood of being prescribed opioids to manage their chronic pain and a decreased likelihood of receiving prescription medications to manage migraines, rheumatoid arthritis, and osteoarthritis.Conclusions These results suggest that individuals with lower socioeconomic status do not receive equal prescription medicine opportunities to manage their chronic pain conditions. This is influenced by a variety of intersecting variables, including access to care, the potential unaffordability of certain therapies, patients' health literacy, and prescribing biases. Future research is needed to identify interventions to improve equity of access to therapies for patients with chronic pain living in lower socioeconomic situations as well as to explain the mechanism through which socioeconomic status affects chronic pain treatment choices by health care providers.Abbreviation SES: socioeconomic status; RA: rheumatoid arthritis; IV: intravenous; SC: subcutaneous; bDMARDs: biological disease-modifying antirheumatic drugs; DMARDS; disease-modifying antirheumatic drugs; TNFi: tumour necrosis factor inhibitors; NSAIDs: non-steroidal anti-inflammatory drugs